Reliability and precision of single frequency bioelectrical impedance assessment of lower extremity swelling following total knee arthroplasty - Loyd, Brian J. (Physiother Theory Pract, 2019)
Total knee arthroplasty (TKA) is the most common elective orthopedic surgery performed in the United States. Following surgery patients experience significant lower extremity swelling that is related to poor satisfaction with surgery and is hypothesized to contribute to functional decline. However, in practice, precise and reliable methods for measuring lower extremity swelling do not exist. The purpose of this study was to provide reliability and precision parameters of an innovative approach, single frequency bioelectrical impedance assessment (SF-BIA), for measuring post-TKA lower extremity swelling. Swelling in 56 patients (64.3 ± 9.3 years; 29 males) was measured before and after TKA using SF-BIA and circumferential measures (CM). Reliability of the measures were calculated using Intraclass Correlation Coefficients (ICC). Precision of the measures were provided using standard error of the measurement and minimal detectable change (MDC90). Change values between time points for SF-BIA and CM are provided. SF-BIA was found to have greater reliability following surgery compared to CM (ICC = 0.99 vs 0.68). SF-BIA was found to have a MDC90 = 2% following surgery, indicating improved ability to detect minute fluctuations in swelling compared to CM (MDC90 = 6%) following surgery. These results indicate that SF-BIA improves the precision and reliability of swelling measurement compared to CM.